Seascape characterization of a Mediterranean vermetid reef: a structural complexity assessment - Picone, Flavio; Chemello, Renato (Frontiers in Marine Science, 2023)
In the Mediterranean Sea, vermetid reefs can modify coastal seascapes forming platforms in the intertidal zone of rocky coasts. With their three-dimensional and seaward-expanding structure, these bioconstructions support high biodiversity levels and provide important ecological functions and ecosystem services. In this study, we perform a first structural characterization of a vermetid reef seascape (hereafter, vermetid reefscape) and quantitatively assess the degree of their contribution to the structural complexity of the coastal seascape. Aerial images of a vermetid reef coast were acquired in the Marine Protected Area of Capo Gallo-Isola delle Femmine (Southern Tyrrhenian Sea) by means of unmanned aerial vehicle technology. In the seascape, the outer reef, platform, and coast classes were identified and digitized in GIS environment. The resulting vermetid reefscape was analysed by means of FRAGSTATS software using metrics belonging to the “area-edge”, “shape”, and “aggregation” categories. To quantitatively assess the structural complexity, the edge density, area-weighted perimeter area ratio, and landscape shape index metrics were applied to the seascapes with and without the vermetid reefs to simulate a sea level rise scenario. In addition, the effect of their presence in terms of coast length (i.e., total edge) was statistically tested using the Wilcoxon signed rank test. The outer reef had the highest total edge value (5,785.6 m) and, at the same time, the lowest class area (1,040 m2). It was also the patchiest, and the most fragmented and geometrically complex class in the seascape. Overall, the bioconstruction positively contributed to the structural complexity of the seascape with higher values of coastal area (12%), edge density (139%), area-weighted perimeter-area ratio (90%), and landscape shape index (66%). The Wilcoxon test revealed a statistically significant effect of the vermetid reefs presence on the coastal total edge (z = 3.9, p < 0.005), with a large effect size (r = 0.74). The results showed an overall higher structural complexity of the vermetid reefscape, indicating that its loss would lead to a significantly less complex seascape, entailing detrimental effects on the supported biodiversity levels and the valuable ecosystem services provided.